Sperm Chromatin Dispersion Test before Sperm Preparation Is Predictive of Clinical Pregnancy in Cases of Unexplained Infertility Treated with Intrauterine Insemination and Induction with Clomiphene Citrate - Vandekerckhove, Frank W. R. C.; De Croo, Ilse; Gerris, Jan; Vanden Abbeel, Etienne; De Sutter, Petra (Frontiers in Medicine, 2016)
Background/Aims: A large proportion of men with normal sperm results as analyzed using conventional techniques have fragmented DNA in their spermatozoa. We performed a prospective study to examine the incidence of DNA fragmentation in sperm in cases of couples with previously unexplained infertility and treated with intra-uterine insemination. We evaluated whether there was any predictive value of DNA fragmentation for pregnancy outcome in such couples. Methods: The percentage of DNA fragmentation and all classical variables to evaluate sperm before and after sperm treatment were determined. We studied the probable association between these results and pregnancy outcome in terms of clinical and ongoing pregnancy rate per started first cycle. We also assessed the optimal threshold level to diagnose DNA fragmentation in our center. Results: When using threshold levels of 20%, 25%, and 30%, the occurrence of DNA fragmentation was 42.9%, 33.3%, and 28.6%, respectively. Receiver operating characteristic (ROC) analysis of all cases revealed an area under the curve (AUC) of 80% to predict the clinical pregnancy rate per cycle from testing the sperm motility (a+b) before treatment. We failed to generate an ROC curve to estimate pregnancy outcome from the amount of DNA fragmentation before treatment. However, when selecting only those men with a pre-treatment DNA fragmentation of at least 20%, the pre-treatment result was statistically different between couples who achieved a clinical pregnancy and those who did not. Conclusion: DNA fragmentation is often diagnosed in couples with unexplained infertility. Each center should evaluate the type of test it uses to detect DNA fragmentation in sperm and determine its own threshold values.